Pleistocene animal communities of a 1.5 million-year-old lake margin grassland and their relationship to Homo erectus paleoecology. Issue 122 (September 2018) - Roach, Neil T.; Du, Andrew; Hatala, Kevin G.; Ostrofsky, Kelly R.; Reeves, Jonathan S.; Braun, David R.; Harris, John W.K.; Behrensmeyer, Anna K.; Richmond, Brian G.
Abstract: The ecological and selective forces that sparked the emergence of Homo 's adaptive strategy remain poorly understood. New fossil and archaeological finds call into question previous interpretations of the grade shift that drove our ancestors' evolutionary split from the australopiths. Furthermore, issues of taphonomy and scale have limited reconstructions of the hominin habitats and faunal communities that define the environmental context of these behavioral changes. The multiple ∼ 1.5 Ma track surfaces from the Okote Member of the Koobi Fora Formation at East Turkana provide unique windows for examining hominin interactions with the paleoenvironment and associated faunas at high spatiotemporal resolution. These surfaces preserve the tracks of many animals, including cf. Homo erectus . Here, we examine the structure of the animal community that inhabited this landscape, considering effects of preservation bias by comparing the composition of the track assemblage to a skeletal assemblage from the same time and place. We find that the track and skeletal assemblages are similar in their representation of the vertebrate paleocommunity, with comparable levels of taxonomic richness and diversity. Evenness (equitability of the number of individuals per taxon) differs between the two assemblages due to the very different circumstances of body fossil versus track preservation. Both samples represent diverse groups of taxa including numerous water-dependent species, consistent with geological interpretations of the track site environments. Comparisons of these assemblages also show a pattern of non-random hominin association with a marginal lacustrine habitat relative to other vertebrates in the track assemblage. This evidence is consistent with behavior that included access to aquatic foods and possibly hunting by H. erectus in lake margins/edaphic grasslands. Such behaviors may signal the emergence of the adaptative strategies that define our genus.